Coccolithophores (calcareous nannoplankton) distribution in the surface waters of the Cretan Straits (South Aegean Sea): productivity and relation with the circulation pattern - Dimiza, M.; Triantaphyllou, M.; Krasakopoulou, E. (Hellenic Journal of Geosciences, 2010)
Living coccolithophores were collected in February 2008, in surface waters from seven stations over the western Cretan Straits (South Aegean Sea, Eastern Mediterranean). The coccolithophore distribution was quantitatively documented through Scanning Electron Microscopy in terms of density, diversity and community structure. In the study period, the most abundant species was Emiliania huxleyi, followed by Rhabdosphaera clavigera and Syracosphaera pulchra, while additional important component of the winter assemblages were Helicosphaera carteri, Algirosphaera robusta and Syracosphaera molischii. The studied coccolithophore communities indicate a close relationship between coccosphere densities and surface water circulation, with the surface temperature gradient affecting species composition.